Comparison of the Antibacterial Activity of Lime Mistletoe Extract (Dendrophthoe petandra (L.) Miq.) Against Staphylococcus aureus with Standard Antibiotics - Lisa Savitri; Mila Putri Daniati; Kharisma Rahmasari; Syntia Tanu Juwita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Staphylococcus aureus remains a major cause of infections worldwide and is increasingly resistant to antibiotics. Natural products, particularly medicinal plants, are valuable sources of alternative antibacterial agents. Lime mistletoe (Dendrophthoe pentandra (L.) Miq.), traditionally used in Indonesian medicine, contains diverse phytochemicals that may exhibit antibacterial activity. Leaves of D. pentandra were collected, dried, and extracted using 96% ethanol. The crude extract was screened for phytochemicals and tested against S. aureus (ATCC 25923) using disk diffusion, broth microdilution, and minimum bactericidal concentration (MBC) assays. Oxacillin and vancomycin served as positive controls, while 1% DMSO was used as a negative control. All tests were performed in triplicate, and data were analyzed using one-way ANOVA with significance set at p < 0.05. Phytochemical analysis revealed the presence of flavonoids, tannins, alkaloids, saponins, and terpenoids. The extract produced inhibition zones of 8.5 ± 0.3 mm, 12.7 ± 0.5 mm, and 16.3 ± 0.6 mm at 25%, 50%, and 100% concentrations, respectively. MIC and MBC values were determined to be 250 µg/mL and 500 µg/mL, with an MBC/MIC ratio of 2, indicating bactericidal activity. Inhibition zones of the extract at its highest concentration were comparable to oxacillin, though vancomycin exhibited superior activity. Ethanol extract of D. pentandra demonstrated moderate yet significant antibacterial activity against S. aureus. Its bactericidal potential and phytochemical diversity support its role as a candidate for further development, especially in topical applications or as a source of active lead compounds. Further research should investigate activity against resistant strains, cytotoxicity, and in vivo efficacy.